From semi-synthetic to natural biomaterials: a journey to the development of an optimized in-vitro model for liver tissue engineering - Tarsitano, Elisa (2022)
Within the liver, tissue resident cells exist in a state of dynamic reciprocity with the extracellular matrix (ECM) whereby the ECM provides structural and biochemical cues to influence cellular functions and cells response by modifying the ECM. To direct cell behaviour, generation of a scaffold with similar biochemical properties to the ECM is therefore highly desirable. One of the main challenges of producing such a scaffold is to find suitable biomaterials that can replicate liver ECM microarchitecture and biochemical complexity.